Nulliparous Individuals with Class III Obesity: Adverse Outcomes with Labor versus Planned Cesarean Delivery - Cagino, Kristen A.; Chen, Han-Yang; Becker, Cabrina; Red, Beverly; Chauhan, Suneet P.; Mendez-Figueroa, Hector (American Journal of Perinatology, 2024)
Individuals with class III obesity (body mass index [BMI] ≥ 40 kg/m2) are at increased risk of cesarean delivery (CD) and peripartum complications. We ascertained compositive neonatal and maternal adverse outcomes among individuals with class III obesity who labored versus had planned CD.This was a retrospective cohort study from 2016 to 2021 using the National Vital Statistics System database. Nulliparous individuals with class III obesity prepregnancy were included if they had singleton, nonanomalous pregnancies and delivered at 37 to 41 weeks of gestation. Individuals were excluded if they had hypertensive disorders or diabetes. The primary outcome was a composite neonatal adverse outcome (CNAO), consisting of Apgar score less than 5 at 5 minutes, assisted ventilation > 6 hours, neonatal seizure, or neonatal death. The secondary outcome was a composite maternal adverse outcome (CMAO) that included admission to the intensive care unit, maternal transfusion, uterine rupture, or unplanned hysterectomy. A sensitivity analysis using a CMAO without transfusion was performed. A multivariable Poisson regression model was performed to calculate adjusted relative risks (aRRs) with 95% confidence intervals (CIs).Of 192,298 individuals who met inclusion criteria, 169,676 (88.2%) labored and 22,622 (11.8%) had a planned CD. Compared with neonates delivered by planned CD, the risk of CNAO was significantly lower in those who delivered after labor (aRR: 0.79, 95% CI: 0.71–0.87). There was no significant difference in the risk of CMAO between groups (aRR: 1.11, 95% CI: 0.87–1.41). However, the risk of CMAO without transfusion was lower in individuals who labored (aRR: 0.57, 95% CI: 0.40–0.83).In nulliparous individuals with class III obesity, the risk of CNAO and of CMAO without transfusion were significantly lower in individuals who labored, versus those who had a planned CD.
Keywords: obesity; neonatal morbidity; maternal morbidity; transfusion; cesarean delivery; labor